PELUANG DAN TANTANGAN PELAKSANAAN PEMBELAJARAN BERDIFERENSIASI DI SEKOLAH DASAR - Ni Putu Suci Pramesti; I Gusti Agung Mastri Mahadewi Widyas Putri; I Wayan Putra Yasa (STKIP Subang, 2025)
Differentiated learning is a crucial instructional method for meeting the diverse characteristics of every student. This study aims to examine the opportunities and constraints in implementing differentiated instruction for fifth-grade students at SD Negeri 2 Sesetan. Participants included the fifth-grade homeroom teacher, Mrs. Yansi Rahayuni Listiari, S.Si., S.Pd., and 28 fifth-grade students. The research utilized a descriptive qualitative approach with data collection techniques consisting of in-depth interviews, classroom observation of the learning process, and analysis of supporting documents. The data analysis process involved the stages of data reduction, data presentation, and conclusion drawing. The findings indicate that the educator continuously implements differentiation in terms of media and teaching methods through the use of videos, visual illustrations, concrete manipulatives, group discussions, peer tutoring, and individual assistance. The practice of content, process, and product differentiation was evident in certain subjects but was not yet fully implemented in the observed Mathematics instruction. Challenges faced by the teacher included time constraints, the demand for creativity, and the lack of an adaptive assessment rubric. This research confirms that the implementation of differentiated learning at SD Negeri 2 Sesetan has positive potential but requires strengthening in the aspects of planning, assessment, and professional support to become more optimal and sustainable.